Case Report: Osteosynthesis-associated infection with Ochrobactrum intermedium after acetabular fracture - Krueger, David Richard; Heller, Karl-Dieter; Trampuz, Andrej; Weenders, Stefan (Frontiers in Surgery, 2024)
Ochrobactrum intermedium (O. intermedium) is a gram-negative, non-fermenting bacterium closely related to Brucella genus. O. intermedium resembles an emergent human pathogen that has rarely been detected in both immunocompetent and immunodeficient patients. A musculoskeletal infection with O. intermedium has not been described in the literature. We present the first case of an osteosynthesis-associated infection (OAI) with O. intermedium in an 80-year-old female patient after osteosynthesis of an acetabular fracture. The patient was admitted to the emergency department 6 months after osteosynthesis of a posterior column acetabular fracture treated via open reduction and internal plate fixation of the posterior column. The patient demonstrated tenderness, redness and swelling at the insertion site as well as a fistula. The radiological controls showed femoral head necrosis and partial protrusion of the head into the pelvis. The laboratory parameters showed no pathological findings. OAI was assumed and a two-stage revision with implant removal and resection arthroplasty in the first stage and hip arthroplasty in the second stage was performed. All microbiological specimens taken at the osteosynthesis site and the hip joint grew O. intermedium. The pathogen was determined using the matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) method. Antibiotic regime consisted of intravenous (IV) meropenem for two weeks followed by oral ciprofloxacin and cotrimoxazole. Implantation of the hip prosthesis was performed 6 weeks after the index surgery using a cementless revision cup and a cemented stem. Meropenem and vancomycin IV were given for one week followed by ciprofloxacin and doxycycline for another 5 weeks. 24 months after the surgery, the patient is infection free and satisfied with the result. With this case report we would like to increase awareness of possible implant-associated bacterial infections caused by O. intermedium.